A DEIXIS ANALYSIS OF SONG LYRICS IN NIKI’S “NICOLE” ALBUM - Rohaili, Alya; Syaputri, Komala Dwi (Premise: Journal of English Education and Applied Linguistics, 2024)
This study aimed to identify the kinds of Deixis and their influence on the formation of meaning in song lyrics. The object of the study was the entirety of the songs under Niki's album, namely, the "Nicole" album. The study examined 12 songs in total. The researchers used a qualitative-descriptive method to do the study as it was considered the best method to describe the analysis result. The result of the study stated that the three kinds of Deixis existed in semantics. There are 99 personal deixes, 15 spatial deixes, and 52 temporal deixis, with 166 deixes. It was identified that the song lyrics from the album mainly used personal. According to the study, Deixis plays an essential role in clarifying the meaning of song lyrics. This study not only offered supplementary information but also provided practical help for readers to comprehend better Deixis, including its various kinds, semantic meanings, and how the use of Deixis was able to influence song lyrics.